Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

find (f o g)(x)
f(x) = 5x+1, g(x)= *square root of x*


Sagot :

Step-by-step explanation:

Hey there!

Here;

f(x) = 5x + 1

g(x) = (√x)

Now;

fog(X) = f(g(x))

= f(√x)

= 5√x + 1

Therefore, fog(X) = 5√x + 1.

Hope it helps!

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.